Bleeding complications in dengue are not associated with significant changes in the modulators of the endothelial barrier - Fernanda Andrade Orsi; Rodrigo Nogueira Angerami; Bruna Moraes Mazetto; Susan Kelly Picoli Quaino; Erich Vinícius de Paula; Joyce Maria Annichino-Bizzachi (Journal of Infection in Developing Countries)
Bleeding complications in dengue may occur irrespective of the presence of plasma leakage. We compared plasma levels of modulators of the endothelial barrier among three dengue groups: bleedings without plasma leakage, dengue hemorrhagic fever, and non-complicated dengue. The aim was to evaluate whether the presence of subtle alterations in microvascular permeability could be detected in bleeding patients. Plasma levels of VEGF-A and its soluble receptors were not associated with the occurrence of bleeding in patients without plasma leakage. These results provide additional rationale for considering bleeding as a complication independent of endothelial barrier breakdown, as proposed by the 2009 WHO classification.